Evaluating Pulp Therapy Provided by Medicaid-participating Pediatric and General Dentists in Georgia from 2010-2019 - Michelle Zin; Beau Meyer; Michael Milano (Georgia Southern University, 2023)
Background: The purpose of this study was to evaluate reimbursable pulp therapy trends in primary teeth performed by general and pediatric dentists. Methods: Aggregate Medicaid claims data from 2010-2019 were obtained from the state of Georgia's Department of Community Health. Two different primary dentition pulp therapy rates were compared between general and pediatric dentists: procedures per provider and children treated per provider. Descriptive statistics, poisson regression, and correlational analysis were performed. Results: Pulp therapy utilization for procedures per provider and children treated per provider decreased (Incidence rate ratio (IRR)=0.97, 95% confidence interval (CI): 0.95 to 0.99; IRR=0.97, 95% CI: 0.94 to 1.01, respectively). The rate differences between general and pediatric dentists were negatively correlated with the number of pediatric dentists. Conclusions: The downward trend in pulp therapy utilization was largely correlated with an increased number of pediatric dentists. This increased access to providers likely contributed to improved oral health utilization. Practical Implications: For a growing workforce, translating clinical guidelines into changes in quality of care may require changes to reimbursement policy.